“The total cost of producing Q units of a given product is given by TC = 500+ 4Q2-12Q Compute Marginal cost and average cost “
The total cost of producing Q units of a given product is given by TC = 500+ 4Q2-12Q. Compute Marginal cost and average cost
Step-by-step explanation:
Write the fraction in simplest form.
12x^2/28x
Answer: (-6x - 5) • (2x + 3)
Step-by-step explanation:
((0 - (22•3x2)) - 28x) - 15
Pull out like factors :
-12x2 - 28x - 15 = -1 • (12x2 + 28x + 15)
Trying to factor by splitting the middle term
3.2 Factoring 12x2 + 28x + 15
The first term is, 12x2 its coefficient is 12 .
The middle term is, +28x its coefficient is 28 .
The last term, "the constant", is +15
Step-1 : Multiply the coefficient of the first term by the constant 12 • 15 = 180
Step-2 : Find two factors of 180 whose sum equals the coefficient of the middle term, which is 28 .
-180 + -1 = -181
-90 + -2 = -92
-60 + -3 = -63
-45 + -4 = -49
-36 + -5 = -41
-30 + -6 = -36
-20 + -9 = -29
-18 + -10 = -28
-15 + -12 = -27
-12 + -15 = -27
-10 + -18 = -28
-9 + -20 = -29
-6 + -30 = -36
-5 + -36 = -41
-4 + -45 = -49
-3 + -60 = -63
-2 + -90 = -92
-1 + -180 = -181
1 + 180 = 181
2 + 90 = 92
3 + 60 = 63
4 + 45 = 49
5 + 36 = 41
6 + 30 = 36
9 + 20 = 29
10 + 18 = 28 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, 10 and 18
12x2 + 10x + 18x + 15
Step-4 : Add up the first 2 terms, pulling out like factors :
2x • (6x+5)
Add up the last 2 terms, pulling out common factors :
3 • (6x+5)
Step-5 : Add up the four terms of step 4 :
(2x+3) • (6x+5)
Which is the desired factorization
Answer: (-6x - 5) • (2x + 3)
3.99 million - 47,000,000
Answer: -43010000.
Step-by-step explanation: 3.99 million is 3,990,000. From there, you subtract 47,000,000 from 3,990,000. The answer is -43010000.
Have a great day! :)
Which polynomial function could be represented by the graph below?
Answer:
C
Step-by-step explanation:Only one that makes sence just look at the graph
PLEASE HELP! 50 POINTS! Consider the following set of sample data: (34, 32, 34, 32, 40, 37, 31, 31, 29, 27). Which of the following will give a 95% t confidence interval for the mean of the population from which the sample was drawn?
Answer:
(15.23,41.016)
Step-by-step explanation:
WE must determine the mean of the data set: Which is the sum of the set divided by the number in the set.
[tex]= (21 + 24 + 25 + 32 + 35 + 31 + 29 + 28)/8 = 225/8 = 28.125[/tex]
We must also determine the standard deviation: Which is the square root of the variance and the variance is the sum of squares of the sample number minus the mean divided by the number if the set data:
[tex]= ((21 - 28.125)^{2} + (24 - 28.125)^{2} +(25 - 28.125)^{2} + (32 - 28.125)^{2} + (35 - 28.125)^{2} + (31 - 28.125)^{2} + (29 - 28.125)^{2} (28 - 28.125)^{2}[/tex]
[tex]= 148.877/8 = 18.6[/tex]
The 95% confidence interval is defined as: The mean ± 1.96*standard deviation divided by the sqaure root of the number of data in the set:
[tex]= 28.125 + (1.96 *18.6)/(\sqrt{8} )[/tex]
[tex]= 41.016[/tex]
[tex]= 28.125 - (1.96 * 18.6)/(\sqrt{8}) = 15.23[/tex]
The confidence interval for this data set is (15.23,41.016)
Answer:
32.7 ± 2.262(1.19)
Step-by-step explanation:
See attached pictures
d If the width of a rectangle with perimeter P is 6 units, what is its length?
Step-by-step explanation:
width is 6 units
P=2(l+w)
p=2(l+6)
l+6=p/2
l= (p/2)-6
The length of the reactangle with a width of 6 units and perimeter p units is (P/2)-6 units.
What is the perimeter of a rectangle?A perimeter is a closed route that surrounds, outlines, or embraces a rectangle. The perimeter of a rectangle is given by the formula,
[tex]\rm Perimeter= 2(Length +width)[/tex]
As it is given that the width of the rectangle is 6 units, while the perimeter of the rectangle is P. Now if we write about the perimeter of the rectangle, it can be written as,
[tex]\rm Perimeter= 2(Length +width)[/tex]
[tex]P = 2(l+6)\\\\\dfrac{P}{2} = (l+6)\\\\l = \dfrac{P}{2}-6[/tex]
Hence, the length of the reactangle with a width of 6 units and perimeter p units is (P/2)-6 units.
Learn more about Perimeter:
https://brainly.com/question/2142493
(2x+3)+(5x17)+90=180
Answer:
x=10
Step-by-step explanation:
Answer:
x is 10 degrees
Step-by-step explanation:
180-90=90
(2x+3)+(5x+17) = 90
7x+20=90
7x=70
x=10
3 lines are shown. A line with points M, H, K intersects a line with points J, H, L at point H. A line extends from point H to point P between angle K H J. Angle M H L is 140 degrees and angle K H P is 20 degrees.
What is mAnglePHJ?
100°
120°
140°
160°
Answer:
120
Step-by-step explanation:
Given:
3 Lines
A line with points M, H, K intersects a line with points J, H, L at point H.
A line extends from point H to point P between angle K H J.
Angle M H L is 140 degrees and angle K H P is 20 degrees.
Solve:
Since, Angle M H L is 140 degrees and angle K H P is 20 degrees.
Then 140 - 20 = 120
Answer is 120
~Lenvy~
Alex had $750,000 he lost 80% how many dollars did he lose
Answer:
$600,000
Step-by-step explanation:
GIven;
Alex had $750,000 he lost 80%
To Find;
How many dollars did he lose
Solve;
$750,000 * 80% = 600,000
Hence, Alex lost $600,000.
~Learn with Lenvy~
Answer:75,000
Step-by-step explanation:he has 750,000 but he loses 80% so he has 75,000 about.
what is the area of a 45 degree sector of a circle with a radius of 12 in.
given ,
a circle of radius 12 inches
and [tex]\theta[/tex] = 45°
now we know that ,
[tex]\\{Area \: of \: sector = \frac{\theta}{360\degree} \times \pi \: r {}^{2} } \\ \\ [/tex]
let's now plug in the values of radius and theta as 12 inches and 45° respectively ,
[tex]\\\dashrightarrow \: \frac{45}{360} \times \frac{22}{7} \times 12 \times 12 \\ \\ \dashrightarrow \: \frac{1}{8} \times \frac{22 \times 12 \times 12}{7} \\ \\ \dashrightarrow \: \frac{22 \times 12 \times 12}{56} \\ \\ \dashrightarrow \: \frac{3168}{56} \\ \\ \dashrightarrow \: 56.57 \: inches {}^{2} (approx.)[/tex]
hope helpful :D
What is the area?
This is 6th grade math
Answer:
Find the base, and then the height of this rhombus;
Base: 7 square units
Height: 7 square units
Multiply your base by the height to get the area;
Because the formula for the area of a rhombus is, A = BH
So,
A = 7(7)
A(area) = 49 square units.
Estimate f(4.04) for f as in the figure
Answer:
2.013 to 3 DP's.
Step-by-step explanation:
f(4.04) will be very close to the tangent line.
Equation of tangent line
is y - 4 = m(x - 10)
m = (4-2) / (10-4) = 1/3
y - 4 = 1/3(x - 10)
y = 1/3x - 10/3 + 4
y = 1/3x + 2/3
So the require estimate of f(4.04)
= 1/3(4.04) + 2/3
= 2.013333
A construction company is building the house shown below. They need to use a scale
of 1 in: 8f (1 inch = 8 feet). They measured the drawing to find that that the height of
the building is 2.5 in.
1.) Explain to the construction workers how they would use this information to
calculate the height of the final building.
2.) What is the height of the final building?
smart.newrow.com is sharing a window
Stop sharing
Hide
Using proportions, we have that:
The height of the building is found using a rule of three.The height is of 20 feet.What is a proportion?
A proportion is a fraction of a total amount, and the measures are related using a rule of three.
The scale is of 1 inch = 8 feet. What is the height for 2.5 inches? The rule of three is given by:
1 inch - 8 feet.
2.5 inches - x feet
Applying cross multiplication, the height in feet of the final building is given by:
x = 8 x 2.5 = 20 feet.
More can be learned about proportions at https://brainly.com/question/24372153
The height of the building is calculated by representing 1 inch as 8 feet. The final building has a height of 20 feet.
What is scaling?Scaling is the increase or decrease in the height of an object by a scale factor k.
Given that the scale used is:
1 inch = 8 feet. Hence:
Since the height of the building is 2.5 in, hence:
Height of the final building = 2.5 in * 8 ft per 1 in = 20 feet
The height of the final building is 20 feet.
Find out more on scaling at: https://brainly.com/question/25722260
[tex] \\ { \rm{If \: }{\tt{A = \left [ \: \begin{array}{ c c c} \: \: \: \: 2 & -3 & - 5 \\ - 1 & \: \: \: 4 & \: \: \: \: 5 \\ \: \: \: \: 1& - 3 & - 4\end{array} \: \: \: \right] \: and \: B = \left[\begin{array}{c c c} \: \: \: \: 2 & - 2 & - 4 \\ - 1 & \: \: \: \: 3 & \: \: \: \: 4 \\ \: \: \: \: 1 & - 2 & - 3\end{array} \right]}}}, { \rm{shown \: that \: AB = A \: and \: BA = B}}[/tex]
[tex] \: [/tex]
Don't Spam
Explain well
Answer:
Given:
[tex] \\ {\tt{A = \left [ \: \begin{array}{ c c c} \: \: \: \: 2 & -3 & - 5 \\ - 1 & \: \: \: 4 & \: \: \: \: 5 \\ \: \: \: \: 1& - 3 & - 4\end{array} \: \: \: \right] \: and \: B = \left[\begin{array}{c c c} \: \: \: \: 2 & - 2 & - 4 \\ - 1 & \: \: \: \: 3 & \: \: \: \: 4 \\ \: \: \: \: 1 & - 2 & - 3\end{array} \right]}}[/tex]
Matrix A is of order 3 × 3 and Matrix B is of order 3 × 3
To Show:
Matrix AB = A , BA = BFormula Used:
[tex]\\ { \rm{ \left[ \begin{array}{c c c} a_{11} & a_{12} & a_{13} \\ a_{21} & a_{22} & a_{23} \\ a_{31} & a_{32} & a_{33}\end{array} \right] \times \left[ \begin{array}{c c c} b_{11} & b_{12} & b_{13} \\ b_{21} & b_{22} & b_{23} \\ b_{31} & b_{32} & b_{33} \end{array} \right] = \: \left[ \begin{array}{c c c} \: \: a_{11}b_{11} + a_{12}b_{21} + a_{13}b_{31} & a_{11}b_{12} + a_{12}b_{22} + a_{13}b_{32} & a_{11}b_{13} + a_{12}b_{23} + a_{13}b_{33} \\ \: \: a_{21}b_{11} + a_{22}b_{21} + a_{23}b_{31} & a_{21}b_{12} + a_{22}b_{22} + a_{23}b_{32}&a_{21}b_{13} + a_{22}b_{23} + a_{23}b_{33} \\ \: \: a_{31}b_{11} + a_{32}b_{21} + a_{33}b_{31}&a_{31}b_{12} + a_{32}b_{22} + a_{33}b_{32} & a_{31}b_{13} + a_{32}b_{23} + a_{33}b_{33}\end{array} \right]}}[/tex]
If A is a matrix of order a×b and B is a matrix of order c×d , then matrix AB exits and is of order a×d , if and only if b = c.
[tex] \: \: [/tex]
If A is a matrix of order a×b and B is a matrix of order c×d , then matrix BA exits and is of order c×b , if and only if d = a.
[tex] \: \: [/tex]
____________________________________________________________________For Matrix AB, a = 3, b = c = 3, d = 3 , thus Matrix AB is of order 3×3
[tex]\\ { \rm{Matrix \: AB = \left[ \begin{array}{c c c} \: \: \: \: 2 & -3 & -5 \\ -1 & \: \: \: 4 & \: \: \: \: 5 \\ \: \: \: \: 1 & -3 & -4 \end{array} \right] \times \left[ \begin{array}{c c c} \: \: \: \: 2 & -2 & -4 \\ -1 & \: \: \: \: 3 & \: \: \: \: 4 \\ \: \: \: \: 1 & -2 & -3 \end{array} \right] = \left[\begin{array}{c c c} \: \: \: \: 2(2)-3(-1)-5(1) & \: \: \: \: 2(-2)-3(3)-5(-2) & \: \: \: \: 2(-4)-3(4)-5(-3) \\ -1(2)+4(-1)+5(1) & -1(-2)+4(3)+5(-2) & -1(-4)+4(4)+5(-3)\\ \: \: \: \: 1(2)-3(-1)-4(1) & \: \: \: \: 1(-2)-3(3)-4(-2) & \: \: \: \: 1(-4)-3(4)-4(-3) \end{array} \right]}}[/tex]
[tex]\\ {\rm{Matrix \: AB = \left[ \begin{array}{c c c} \: \: \: \: 4 + 3 - 5 & \: \: \: -4 -9 + 10 & \: \: -8 - 12 + 15 \\ -2 - 4 + 5 & \: \: \: \: \: \: + 2 + 12 - 10 & \: \: \: \: \: 4 + 16 - 15 \\ \: \: \: \: \: 2 + 3 - 4 & \: \: -2 - 9 + 8 & -4 - 12 + 12 \end{array} \right] = \left[ \begin{array}{c c c} \: \: \: \: 2 & -3 & -5 \\ -1 & \: \: \: \: 4 & \: \: \: 5 \\ \: \: \: \: 1 & -3 & -4 \end{array} \right]}}[/tex]
[tex]\\ {\rm{Matrix \: AB = \left[ \begin{array}{c c c} \: \: \: \: 2 & -3 & -5 \\ -1 & \: \: \: \: 4 & \: \: \: 5 \\ \: \: \: \: 1 & -3 & -4 \end{array} \right] = Matrix \: A}}[/tex]
Matrix AB = Matrix A____________________________________________________________________For Matrix BA, a = 3, b = c = 3, d = 3 , thus Matrix BA is of order 3 × 3
[tex]\\ {\rm{Matrix \: BA = \left[ \begin{array}{c c c} \: \: \: \: 2 & -2 & -4 \\ -1 & \: \: \: \: 3 & \: \: \: \: 4 \\ \: \: \: \: 1 & -2 & -3 \end{array} \right] \times \left[ \begin{array}{c c c} \: \: \: \: 2 & -3 & -5 \\ -1 & \: \: \: \: 4 & \: \: \: \: 5 \\ \: \: \: \: \: 1 & -3 & -4 \end{array} \right]}}= \left[ \begin{array}{c c c} \: \: \: \: \: 2(2) -2(-1) -4(1) & \: \: \: \: 2(-3) -2(4) -4(-3) & \: \: \: \: 2(-5) -2(5) -4(-4) \\ \: -1(2) + 3(-1) + 4(1) & -1(-3) + 3(4) +4(-3) & -1(-5) + 3(5) + 4(-4) \\ \: \: \: \: \: 1(2) -2(-1) -3(1) & \: \: \: \: 1(-3) -2(4) -3(-3) & \: \: \: \: 1(-5) -2(5) -3(-4) \end{array} \right][/tex]
[tex]\\{ \rm{Matrix \: BA = \left[ \begin{array}{c c c} \: \: \: \: 4 + 2 - 4 & \: \: \: -6 -8 + 12 & \: \: -10 - 10 + 16 \\ -2 - 3 + 4 & \: \: \: \: \: \: +3 + 12 - 12 & \: \: \: \: \: + 5 + 15 - 16 \\ \: \: \: \: \: 2 + 2 - 3 & \: -3 -8 +9 & \: \: \: \: \: -5 -10 + 12 \end{array} \right] = \left[ \begin{array}{c c c} \: \: \: \: 2 & -2 & -4 \\ -1 & \: \: \: \: 3 & \: \: \: \: 4 \\ \: \: \: \: 1 & -2 & -3 \end{array} \right]}}[/tex]
[tex]\\{ \rm{Matrix \: BA = \left[ \begin{array}{c c c} \: \: \: \: 2 & -2 & -4 \\ -1 & \: \: \: \: 3 & \: \: \: \: 4 \\ \: \: \: \: 1 & -2 & -3 \end{array} \right] = Matrix \: B}}[/tex]
Matrix BA = Matrix B____________________________________________________________________Use Demos Graphing Calculator
Rob works part time at the Fallbrook Riding Stable. He makes $5 an hour exercising
horses and $10 an hour cleaning stalls. Because Rob is a full-time student, he can
work no more than 12 hours per week. However, he must make at least $60 per
week.
Which of the following is a possible solution for this system of inequalities?
A. 1 hour exercising and 1 hour cleaning
B. Two hours exercising and five hours of cleaning
C. Seven hours of exercising and eight hours of cleaning
D. Two hours exercising and eight hours cleaning
Answer:
D. Two hours exercising and eight hours cleaning
Step-by-step explanation:
Rob works part time at the Fallbrook Riding Stable. He makes $5 an hour exercising horses and $10 an hour cleaning stalls. Because Rob is a full-time student, he can work no more than 12 hours per week. However, he must make at least $60 per week.
x = hrs. exercising horses
y = hrs. cleaning stalls
Equations:
Hours he can work per week:
x + y ≤ 12
Amount of money he can make per week:
5x + 10y ≥ 60
Now, graph your equations into desmos.
As you can see in the graph, the correct answer is D (2, 8)
Check your answer by hand:
x + y ≤ 12
2 + 8 ≤ 12
10 ≤ 12
This statement is correct
5x + 10y ≥ 60
5(2) + 10(8) ≥ 60
10 + 80 ≥ 60
90 ≥ 60
This statement is correct
Therefore, the correct answer is D
Hope this helps!
Given m \| nm∥n, find the value of x. (7x-10)° (6x-5)°
7x-10=6x-5
We simplify the equation to the form, which is simple to understand
7x-10=6x-5
We move all terms containing x to the left and all other terms to the right.
+7x-6x=-5+10
We simplify left and right side of the equation.
+1x=+5
We divide both sides of the equation by 1 to get x.
x=5
Urgente!!! Doy 20 puntos
Answer:
74-7, 0, +9Step-by-step explanation:
Hope this helps
Yesterday, Salma had 387 baseball cards. Today, she gave 141 away. How many cards does Salma have left?
Answer:
387-141=246
Step-by-step explanation:
387
- 141
-------------
246
For a sample of n = 16 scores, what is the value of the population standard deviation (o) necessary to produce each of the following standard error values?
a. Ом = 8 points
b. Ом =4 points
с. Ом = 1 point
Using the Central Limit Theorem, it is found that the values of the population standard deviation [tex]\sigma[/tex] needed are given by:
a) [tex]\sigma = 32[/tex]
b) [tex]\sigma = 16[/tex]
c) [tex]\sigma = 4[/tex]
What does the Central Limit Theorem state?By the Central Limit Theorem, the sampling distribution of sample means of size n has standard error [tex]s = \frac{\sigma}{\sqrt{n}}[/tex].
In this problem, we have that n = 16.
Item a:
s = 8, hence:
[tex]s = \frac{\sigma}{\sqrt{n}}[/tex]
[tex]8 = \frac{\sigma}{\sqrt{16}}[/tex]
[tex]\sigma = 32[/tex]
Item b:
s = 4, hence:
[tex]s = \frac{\sigma}{\sqrt{n}}[/tex]
[tex]4 = \frac{\sigma}{\sqrt{16}}[/tex]
[tex]\sigma = 16[/tex]
Item c:
s = 1, hence:
[tex]s = \frac{\sigma}{\sqrt{n}}[/tex]
[tex]1 = \frac{\sigma}{\sqrt{16}}[/tex]
[tex]\sigma = 4[/tex]
More can be learned about the Central Limit Theorem at https://brainly.com/question/24663213
HELP ME OUT PLS!!!!!!!
The model represents an equation. What value of x makes the equation true?
A) 15/4
B) 15/8
C) -15/4
D) -15/8
Answer:
B
Step-by-step explanation:
-6x + 6 = 2x - 9
-6x + 15 = 2x
15 = 8x
x = 15/8
Jack is 3 times as old as Lacy. 9 years ago the sum of their ages was 22 . How old are they now?
Answer:
Jack is 31
Lacy is 10
Step-by-step explanation:
x - 9 = 22
since jack is 3 times as old as lacy,
the formula is
3x - 9 = 22
3x = 31
x = 10.3
So Jack is 31
And Lacy is 10
To prove this, subract 9 (years) from both ages
It will give you an approximate sum of 22 years for both their ages, as the question states
Since Lacy is a little over 10 years old, Jack is 31 instead of 30
The formula was taken from someone elses answer so sorry if it`s wrong
[tex]x^{2} -36\frax+5/(x+6)[/tex]
the answer is
x^{2}-31x+5b
Three times a number x is more than 18.
Answer:
3x>18
Step-by-step explanation:
Three times the number x will be called 3x. If an expression is more or greater than a number, we use the greater symbol: >
So, we can write,
3x>18
Find the slope and y-intercept for the graph of the equation
6x - 4y = -36
Answer:
[tex]y = \dfrac{3}{2} x + 9[/tex]
Step-by-step explanation:
We would like to write the given equation in slope intercept form of the line .
[tex]\longrightarrow 6x - 4y = -36 [/tex]
The slope intercept form of the line is [tex] y = mx + c [/tex] , where
[tex] m[/tex] is the slope [tex] (x,y)[/tex] is a point on the line .[tex] c [/tex] is the y intercept .we can rewrite the given equation as ,
[tex]\longrightarrow 6x - 4y = -36 \\ [/tex]
[tex]\longrightarrow -4y = -36 -6x \\ [/tex]
[tex]\longrightarrow -4y = -6( x + 6)\\[/tex]
[tex]\longrightarrow y =\dfrac{-6}{-4}(x + 6)\\[/tex]
[tex]\longrightarrow y = \dfrac{3}{2}(x+6)\\ [/tex]
[tex]\longrightarrow y = \dfrac{3}{2}x +\dfrac{3}{2}\times 6\\[/tex]
[tex]\longrightarrow \underline{\underline{\pmb{ y =\dfrac{3}{2}x +9}}}{}[/tex]
This is the required equation of line in slope intercept form , with ;
[tex]m = \dfrac{ 3}{2} [/tex][tex]c = 9[/tex]Answer:
Refer to the attachment
Help ASAP.
i need you to please break it down ive tried and just don't understand
Answer:
A) -4
Step-by-step explanation:
Question
[tex]\sf evaluate \ \dfrac{-4+(m+2)}{n} \ \sf when \ m=\dfrac23 \ and \ \sf n=\dfrac13[/tex]
Solution
Substitute the given values of m and n into the original expression:
[tex]\sf \implies \dfrac{-4+(\frac23+2)}{\frac13}[/tex]
Carry out the operation in the brackets first [tex]\sf (\frac23+3)=\frac83[/tex]
[tex]\sf \implies \dfrac{-4+\frac83}{\frac13}[/tex]
Now carry out the operation in the numerator [tex]-4+\frac83=-\frac43[/tex]
[tex]\sf \implies \dfrac{-\frac43}{\frac13}[/tex]
Dividing by a fraction is the same as multiplying by the flipped version of the fraction (flipped = swap the numerator and denominator of the fraction we are dividing by):
[tex]\sf \implies -\dfrac43 \div \dfrac13=-\dfrac43 \times \dfrac31[/tex]
To multiply a fraction, simply multiply the numerators and multiply the denominators:
[tex]\sf \implies -\dfrac43 \times \dfrac31=\dfrac{-4 \times 3}{3 \times 1}=-\dfrac{12}{3}[/tex]
Finally simplify:
[tex]\sf \implies -\dfrac{12}{3}=-4[/tex]
Triangle ABC was dilated and translated to form similar triangle A'B'C'.
On a coordinate plane, 2 triangles are shown. Triangle A B C has points (0, 2), (2, 2), and (2, 0). Triangle A prime B prime C prime has points (negative 4, negative 1), (1, negative 1), and (1, negative 6).
What is the scale factor of the dilation?
One-fifth
Two-fifths
Five-halves
5
Answer:
C
Step-by-step explanation:
Help picture below problem 10
Answer:
180-52=128
Do mark BRAINLIEST
Given mſn, find the value of x.
(6x-7)º
m
(4x-10°
Answer:
x = 3
Step-by-step explanation:
These angles are actually equal to each other
This is because when two lines intersect, the two opposite angles are the same.
Since they are the same, you can set them equal to each other
Like so:
6x - 7 = 4x - 1
Then solve:
6x - 7 = 4x - 1
6x = 4x +6
2x = 6
x = 3
Andrew drinks 1.9 litres of water each day for three years. By rounding the amount of water an the number of days to one significant figure find the approximate amount of water he drinks during the three years. [One year = 365 or 366 days]
Answer:
2081days or 2086days
Step-by-step explanation:
1.9(365)=693.5
1.9(366)=695.4
693.5(3)=2080.5
695.4(3)=2086.2
What is a number greater then 0.6 but less than 0.7
Answer:
0.65 is a number greater than 0.6 but less than 0.7